ANALYSIS OF EFFECTIVENESS AND PARKING LEVY GAP IN MALANG REGENCY - Martha Ignatia Hendrati; Hadi Sumarsono (Journal of Economics, Business, and Accountancy Ventura, 2012)
In connection with the efforts to promote and explore the sources of local revenues, the governmentof Malang Regency has now been trying to increase the revenues. This effort is intendedto make the local government not to be dependent much on the central government.This study attempts to analyze the effectiveness the problems that exist in parking fees in orderto see the real potential and some suggestions for policies related to the increase of thelocal government income. It was conducted in Malang regency, which was chosen by meansof a purposive random sampling. It shows as the following. (1) The potential of Malang Regencyparking levy is totally up to Rp 1,618,939,100. It can be compared with the realizationof 2009 that was up to the figure of Rp 225,842,000, and therefore the effectiveness is13.95%; (2) The results of the SWOT analysis showed that the position of an increase of incomein parking levies and service market is in quadrant 2 (two), this means a dominance ona combination of factors both strengths and barriers. It is suggested that the government increaseof the effectiveness of withdrawal by doing some efforts as described in this study.